Proteomics, Bioinformatics and Structure-Function Antigen Mining For Gonorrhea Vaccines - Baarda, Benjamin I.; Martinez, Fabian G.; Sikora, Aleksandra E. (Frontiers in Immunology, 2018)
Expanding efforts to develop preventive gonorrhea vaccines is critical because of the serious health consequences combined with the prevalence and the dire possibility of untreatable gonorrhea. Reverse vaccinology, which includes genome and proteome mining, has proven successful in the discovery of vaccine candidates against many pathogenic bacteria. Here, we describe proteomic applications including comprehensive, quantitative proteomic platforms and immunoproteomics coupled with broad-ranging bioinformatics that have been applied for antigen mining to develop gonorrhea vaccine(s). We further focus on outlining the vaccine candidate decision tree, describe the structure-function of novel proteome-derived antigens as well as ways to gain insights into their roles in the cell envelope, and underscore new lessons-learned about the fascinating biology of Neisseria gonorrhoeae.